Effect of surface properties of activated carbon fiber cathode on mineralization of antibiotic cefalexin by electro-Fenton and photoelectro-Fenton treatments: Mineralization, kinetics and oxidation products. (April 2019) - Zhang, Yanyu; Wang, Aimin; Ren, Songyu; Wen, Zhenjun; Tian, Xiujun; Li, Desheng; Li, Jiuyi
Abstract: Solutions of 200 mg L −1 cefalexin (CLX), an antibiotic with high usage frequency and biodegradation resistance, have been comparatively degraded by electro-Fenton (EF) and photoelectro-Fenton (PEF) processes using two kinds of activated carbon fiber (ACF) cathodes with different physical properties. These two ACFs shared similar pore volumes and pore diameters but varied BET surface areas, which were confirmed to be 0.5210 cm 3  g −1, 2.26 nm and 921 m 2  g −1 for ACF1, while 0.6508 cm 3  g −1, 2.16 nm and 1206 m 2  g −1 for ACF2, respectively. Their oxidation abilities were comparatively assessed in terms of degradation kinetics and mineralization rates, which increased in the order: ACF1-EF < ACF2-EF < ACF1-PEF < ACF2-PEF. These results confirmed the superiority of ACF with higher surface area, which was correlated to faster H2 O2 and OH accumulation in more reaction sites provided. After 120 min electrolysis, ACF1 exhibited 1510 μM H2 O2 and 37 μM OH accumulation, while ACF2 generated 1934 μM H2 O2 and 85 μM OH. Moreover, ACF cathode with more developed pore structure also revealed faster formation of degradation by-products like inorganic ions (NH4 + and NO3 − ions) and short-chain carboxylic acids (acetic, formic, oxamic and oxalic acids), as well as enhanced removal for partial acids. In order to gain a deeper understanding of degradation mechanisms for ACF2-PEF system, evolutions of six aromatic by-products generated from sulfoxidation, hydroxylation and decarboxylation were confirmed by UPLC-QTOF-MS/MS determination. Based on the above identifications of the degradation intermediates, a plausible reaction pathway for CLX removal was proposed. Graphical abstract: Image 1 Highlights: Cefalexin was degraded by EAOPs with varied surface properties ACF cathodes. Faster decay and higher mineralization achieved by larger specific area cathode. ACF with higher specific area could promote H2 O2 and OH production. Quicker by-products formation and elimination attained in more porous ACF cathode. 6 aromatic products were detected and a plausible reaction pathway was proposed.